Soil quality in two coffee crop systems in the Amazon biome - Nirvani S. Henrique; Katia L. Maltoni; Glaucia A. Faria (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The form of occupation of the state of Rondônia, Brazil, favored the extensive agriculture, which resulted in a fast deforestation. The removal of forests and inadequate soil management and use, combined with a hot and wet climate, affected the soil chemical, physical, and biological attributes. In search for less impacting and alternatives that promote greater soil conservation for coffee production in the North region of Brazil, the objective of this work was to evaluate the effects of two coffee crop systems on the soil chemical and microbiological attributes. The treatments consisted of a shaded coffee crop (SCC) and a full-sun coffee crop (FCC). A completely randomized design was used, with four clusters per treatment and seven sampling points per cluster, which constituted a replication, totaling 28 replications per treatment. The data were collected in April 2018, in a rural property in the municipality of Cacoal, state of Rondônia, Brazil (11º21’50’’S, 61º20’10’’W, and altitude of 238 m). The soil organic matter, pH, P, K, Ca, Mg, Al, H+Al, base saturation, and basal respiration were determined. The soil under SCC had higher Ca content, pH, and base saturation, and lower potential acidity (H+Al) and Al content than that under FCC. The litterfall on the soil under FCC presented higher N and Mg contents. The soil basal respiration increased in the first 5 cm depth in the treatment with SCC.